Relationship between cladoceran (Crustacea) functional diversity and lake trophic gradients. (19th September 2016) - Nevalainen, Liisa; Luoto, Tomi P.
Summary: Functional diversity (FD) as a biodiversity measure has an explicit role in ecosystem functioning because the effects of environmental changes in ecosystems are determined by biological functions, such as feeding type and trophic position, of particular species. We evaluated the usability of functional characterization and FD of an aquatic keystone group (Crustacea: Cladocera) for enhancing the understanding of long‐term lake functional responses to environmental changes. The aims were to separate ecologically significant functional groups, investigate succession of such functional groups during nutrient enrichment process and determine the relationship between FD and lake productivity using a palaeolimnological approach. We selected two eutrophicated study lakes from southern Finland for down‐core investigations, one with a centennial (past c . 350 years) and the other with a decadal (past c . 70 years) nutrient enrichment record. Cladoceran microfossils in the sediment cores were used to determine the taxonomic structure of the past communities. Ecologically relevant functional characteristics were determined to separate functional groups by utilizing a functional dendrogram and a weighted community‐based FD index together with a set of multidimensional FD indices. The indices were applied to the down‐core assemblages. The functional dendrogram separated cladocerans into functional groups where habitat type principally separated open‐water filterers and predators from epibenthic scrapers and detritivores. Further separation in the pelagic branch was based on body size and feeding and among the benthic branch body shape. Functional assemblages changed markedly during the nutrient enrichment process. In the early stage of eutrophication, the largest functional changes were caused by small planktonic filterers and predators. Small filterers and epibenthos responded strongest during the eutrophic–hypereutrophic succession. FD had a positive long‐term relationship with lake trophic status until eutrophic conditions that was likely caused by diversifying resources and versatile food webs. Under hypereutrophic conditions, and especially at a decadal temporal resolution, alternating predation regimes caused variance to FD. In the current records, cladoceran FD was positively related to lake productivity and bottom‐up controls during the early stages of eutrophication in the long‐term record but top‐down controls apparently were more important at a decadal scale and under hypereutrophic conditions. Abstract : Lay Summary